Enhancing Vocational Competency Exam Preparation: The Impact of YouTube Channel Videos - Tri Umaroh, Susi; Soeryanto; Warju; Suwito, Djoko; Suprianto, Bambang; Rizky, Sudirman; Ariyanto (IJER (Indonesian Journal of Educational Research), 2023)
This study aimed to assess the effectiveness of using YouTube Channel videos as a learning tool, with a specific focus on tire changing and wheel balancing content, to enhance student learning outcomes and prepare them for the Vocational Competency Exam at Vocational High Schools. The research was conducted at Dharma Bahari Vocational School in Surabaya, where blended learning was adopted in response to the COVID-19 pandemic. The research utilized a quantitative descriptive research design, incorporating response questionnaires from both students and teachers, as well as cognitive, affective, and psychomotor assessment instrument sheets. Data collection included questionnaires, tests, and observations, followed by quantitative descriptive analysis. The findings of the study indicated a significant positive impact of using YouTube Channel video media on student learning outcomes. This impact was evident through the noteworthy difference in student learning outcomes before and after the intervention. The significance value (p-value) in the t-test was 0.000, falling below the probability threshold of 0.05, signifying a substantial difference in the learning outcomes of students who utilized YouTube Channel video media. In conclusion, this research affirms that YouTube Channel can effectively serve as a supportive tool in blended learning and as a means of preparing students for vocational competency exams. as a result, the recommendation stemming from this research is to continue harnessing YouTube Channel video media for learning purposes and to explore the development of video content relevant to other materials.